Secondary traumatization in criminal justice professions: a literature review. Issue 4 (21st April 2023) - Ko, Hayley; Memon, Amina
ABSTRACT: Professionals working in the criminal justice sector are vulnerable to sources of indirect trauma such as the interactions with perpetrators of crime who themselves may be traumatised and exposure to distressing events or graphic material. This systematic review aims to examine the prevalence of this secondary traumatization and related resilience and risk factors among criminal justice professions. After identifying 158 relevant studies within PubMed, Scopus, Web of Science, PsycINFO, and Cochrane, 52 studies were included in this review. Low to moderate levels of secondary traumatization was reported in criminal justice professions. The low prevalence of secondary traumatization may be explained by social desirability and the stigma of mental health issues in these professions. Risk factors (i.e. history of mental illness, work-related trauma, negative coping strategies) predicted secondary traumatization. Support strategies and interventions were moderately effective, however further research and a consensual definition of secondary traumatization is needed, so that organisations may benefit from trauma-informed approaches.